Lysimachus a study in early Hellenistic kingship - Lund, Helen S. (Routledge, 1992)
Among Alexander's successors, Lysimachus is the forgotten man; when he is recalled it is usually as a brutal oppressor of the Greeks, or conversely, as a mediocre man spurred into action only late in life by a domineering woman. As the first full-length study of Lysimachus in the English language, this book aims to reassess Lysimachus achievement, which although ephemeral, foreshadowed the growth of the Pergamene and Byzantine empires